Knowledge Analysis on Logistics Cost Trade-Offs: A Study With Portuguese Food Sector’ Professionals - Cordeiro Pereira, Ana Luiza; Novais Almeida dos Santos Martins, Alexandra Manuela; Veloso Santos Policarpo, Renata; Ribeiro Pereira, Maria Teresa (International Journal of Industrial Engineering and Management, 2018)
Logistics is an important area in the economic-financial performance of companies, which makes it necessary to analyse their costs, as well as the trade-offs between them. Thus, the present study, with the objective of analysing the Portuguese food sector logistic professionals’ knowledge regarding to logistics costs trade-offs and their impact on the economic-financial performance of the organizations, showed that there are gaps concerning this subject. Throughout the structured interview and by using the SPSS software, the study shows the existence of flaws in the practical application of the trade-offs’ theory, such as the pressure from the managers for individual cuts in costs; and points out trade-offs of logistical costs relevant to the food sector. These results contribute to the expansion of studies on the subject, besides providing a perspective of the compensatory exchanges that can contribute to the decision making in relation to the costs concerning logistics activities. Article history: Received (16.05.2018); Revised (29.06.2018); Accepted (03.09.2018)